2007
DOI: 10.1111/j.1526-4610.2007.00867.x
|View full text |Cite
|
Sign up to set email alerts
|

A Double‐Blind, Dose Comparison Study of Topiramate for Prophylaxis of Basilar‐Type Migraine in Children: A Pilot Study

Abstract: Preventive therapy with topiramate resulted in reducing the overall migraine frequency and the frequency of attacks of BM at both 25 mg and 100 mg doses relative to the historical baseline and prospective baseline periods. The 2 treatment groups resulted in comparable outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 13 publications
1
32
0
2
Order By: Relevance
“…Triptans are contraindicated in BTM because of theoretical risks of vasospasm and stroke. 37,44,45 Benign Paroxysmal Vertigo of Childhood Benign paroxysmal vertigo of childhood, as a subtype of childhood periodic syndromes in migraine, is characterized by onset between 1 and 4 years, abrupt randomly occurring attacks of vertigo and imbalance often with nausea and vomiting that lasts from 30 seconds to 20 minutes, usually unaccompanied by headache. Episodes begin suddenly with a sensation of anxiety and fear, and may be associated with pallor, nausea, or diaphoresis.…”
Section: Basilar-type Migraine (Btm)mentioning
confidence: 99%
See 1 more Smart Citation
“…Triptans are contraindicated in BTM because of theoretical risks of vasospasm and stroke. 37,44,45 Benign Paroxysmal Vertigo of Childhood Benign paroxysmal vertigo of childhood, as a subtype of childhood periodic syndromes in migraine, is characterized by onset between 1 and 4 years, abrupt randomly occurring attacks of vertigo and imbalance often with nausea and vomiting that lasts from 30 seconds to 20 minutes, usually unaccompanied by headache. Episodes begin suddenly with a sensation of anxiety and fear, and may be associated with pallor, nausea, or diaphoresis.…”
Section: Basilar-type Migraine (Btm)mentioning
confidence: 99%
“…BTM is the most common migraine "variant," representing 3% to 19% of migraine, and affects all age groups and both sexes. 44,45 The International Headache Society criteria for BTM require the presence of 1 or more preceding aura symptoms. The aura generally lasts up to <1 hour and is usually followed by a headache that may be occipital.…”
Section: Basilar-type Migraine (Btm)mentioning
confidence: 99%
“…After open study by Pascual et al [5] on lamotrigine use for the preventive treatment of selected patients with disturbing migraine auras, including those with BM and hemiplegic migraine, no other clinical trials have been reported in the literature. Other anticonvulsant drugs have been tested in BM such as sodium valproate [6] and topiramate in a child population [7] with a good response at both 25 and 100 mg doses. More recently, acetazolamide [8] relieved BM attacks in a reported patient with both BM and episodic ataxia type 2 and a novel nonsense mutation in CACNA1A gene at codon position 583.…”
Section: Discussionmentioning
confidence: 99%
“…Preventative treatment with calcium channel blockers or topiramate can be considered 25 26. β-Blockers and triptans are contraindicated by some in case they exacerbate ischaemia by vasoconstriction, although recent studies have found triptans to be safe and effective in basilar migraine 27…”
Section: Causesmentioning
confidence: 99%